Baseline susceptibility of Mediterranean strains of Trialeurodes vaporariorum (Westwood) to cyantraniliprole. Issue 7 (7th March 2018) - Moreno, Inmaculada; Belando, Ana; Grávalos, Carolina; Bielza, Pablo
Abstract: BACKGROUND: Cyantraniliprole is a novel anthranilic diamide insecticide that acts on a broad spectrum of insect pests, exclusively by activating their ryanodine receptors. Cyantraniliprole is very effective against whitefly and it presents a favorable ecotoxicological profile. In this study, the baseline susceptibility to cyantraniliprole of Trialeurodes vaporariorum populations from the Mediterranean area was established in nymphal systemic uptake bioassays. RESULTS: The bioassay data showed that the susceptibility to cyantraniliprole varied among the strains collected across the Mediterranean basin. The 50% lethal concentration (LC50 ) range of cyantraniliprole for 16 field populations was from 0.017 to 0.194 mg L ‐1, a 11.4‐fold natural variability between the least and most sensitive populations. These LC50 values are similar to those reported in a previous study of the use of cyantraniliprol against another species of whitefly, Bemisia tabaci [LC50 = 0.048 (0.034–0.063) mg L ‐1 ]. CONCLUSION: The current study confirmed the effectiveness of cyantraniliprole against T. vaporarioum strains, adding to the evidence that cyantraniliprole is a promising tool for use in integrated pest management programs. Future shifts in the susceptibility of whitefly field populations to cyantraniliprole may be documented according to the baseline susceptibility range of the populations tested in this research. © 2018 Society of Chemical Industry Abstract : Cyantraniliprole is a novel diamide insecticide that acts on a broadspectrum of insect pests. In this article, the baseline susceptibility to cyantraniliprole of Mediterranean populations of T. vaporariorum was established.